Three new species of the genera Ceraclea Stephens and Setodes Rambur (Trichoptera: Leptoceridae) from Laos and Cambodia - Laudee, Pongsak; Malicky, Hans; Takenaka, Masaki; Suwannarat, Nannaphat; Kong, Chamroeun; Vongswombath, Chanda; Tojo, Koji (Zootaxa, 2024)
Three new species of Leptoceridae were described from the Lower Mekong tributaries, namely Ceraclea luangnamthaensis n. sp., Setodes xangthevadaensis n. sp. from Laos, and Setodes mongkondechsawati n. sp. from Cambodia. The male genitalia of Ceraclea luangnamthaensis n. sp. are distinguished from those of other species by its preanal appendages, which are circular in lateral view. The male genitalia of Setodes xangthevadaensis n. sp. are distinguished from those of other species by their segment X, which is separated into a trifurcate apicodorsal process and two long slender apicolateral processes in dorsal view. The male genitalia of Setodes mongkondechsawati n. sp. are distinguished from those of other species by the apicodorsal process of segment X which is circular in dorsal view.